Preclinical evidence of Malay traditional herbal supplement for diabetes - Abdul Majid, Fadzilah Adibah; Teh, L. C; Sayid Abdullah, S.H.A; Ahmad, Rabiatul Adawiyah; Bakhtiar, M. Taher; Abdul Wahid, Mohd Effendy (http://www.ishs.org/ishs-article/1125_32, 2016)
In this report, one herbal folk recipe traditional claim for diabetes treatment, jamu KM is subjected to scientific studies. The exposure of traditional diabetes decoction, KM extract to 3T3-L1 at 1 mg mL-1 shows significant increase in glucose uptake with no LD50 value. 150 μg mL-1 methanolic extract of Jamu KM yield intense lipid droplet accumulation in non-insulin induced adipocytes 3T3-L1. Further investigation through in vivo study of KM extract using diabetic Spraque Dawley rats indicates reduction in blood glucose at the concentration of 0.05 g kg-1 body weight (bwt). A similar response was observed with the treatment using glibenclamide at 0.006 g kg-1 bwt. Histopathological data show increase in the relative organ weight (g 100 g-1 bwt) of liver and kidney of all diabetic rats as compared to normal group while pancreas was not affected. However, glibenclamide treated group shows 14 and 15% larger liver and kidney, respectively, than the other diabetic groups and jamu KM treated. This finding is a promising approach in validation of herbal medication from the past wisdom through modern techniques.